Circulating exosomes in sepsis: A potential role as diagnostic biomarkers, therapeutic and drug delivery carriers - Roushka Bhagwan Valjee; Usri H. Ibrahim; Kwanele Xulu; Saajida Mahomed; Irene Mackraj (Smart Materials in Medicine, 2023)
Sepsis and sepsis-related organ dysfunction have been identified as significant global life-threatening health threats, with a high mortality rate despite ongoing research in the area. Timely diagnosis is essential such that treatment could be initiated as early as possible to ensure the best outcome, since delayed intervention is associated with a higher mortality. Patient stratification and disease monitoring, present significant challenges in sepsis treatment and management strategies, largely due to the heterogenicity of sepsis signs and symptoms. Hence a focus on potential biomarkers to overcome these challenges is needed. Recently, extracellular vesicles (EVs), mainly the exosome subtype, have been investigated regarding their potential role in sepsis diagnostics, therapeutics and as drug delivery vehicles. Herein, we present an up-to-date review covering the role of circulating exosomes in the diagnosis and monitoring of the progression of sepsis and in therapeutics and drug delivery for sepsis. To provide context, sepsis pathophysiology and the role of circulating exosomes in sepsis have been highlighted. Future prospects, current challenges and recommendations regarding the role of exosomes in sepsis are also identified.